(untitled) (Research, Society and Development, 2020)
This study aims to seek an understanding of the role and importance of the school psychologist in the face of the demands of adolescence, in addition to discussing the main challenges faced by these professionals in this area, based on the first season of the “13 Reasons Why” series. In this way, it seeks to sensitize people about the need to have a more sensitive and welcoming look, aiming to promote quality mental health in the school environment. The series shows the context that many teenagers experience in their schools, from problems with drug use to sexual abuse, aggression and lack of empathic adults seeking to understand and help them. The literature review was used as a research methodology, making it possible to understand the importance of the school psychologist, acting with qualified and welcoming listening to adolescents in their demands. Bearing in mind that they are in a phase permeated by doubts, in which the transformations experienced cause restlessness and strangeness in relation to themselves, they need a qualified help, which is given by the professional of Psychology. It is in this sense that schools become important places for discussing topics considered taboo, such as suicide, in view of the large number of adolescents who attend it. Challenges that are still often encountered by psychologists are the lack of open spaces for action in the school environment and questions about their functions, requiring greater visibility for this area of ​​expertise. It was found in this work that the series can make the adolescents identify with the topics covered and then start talking more about their feelings, especially in the school environment, where they spend most of their time, being able to exchange experiences with others. But, for this to happen, it is necessary that the school recognizes such importance and starts to insert the Psychology professional in its staff.